The medical supervision of infants in the children’s out-patient department : methodical instructions for students of 6 course of medical faculty - Panko, N. О.; Zimnytskа, T. V.; Панько, Наталія Олександрівна; Зімницька, Тетяна Василівна (Kharkiv : V. N. Karazin national university, 2018)
Methodical recommendations provide information on the dynamic observation of children under 3 years of age in polyclinic conditions, which includes assessment of physical and psychomotor development, prophylactic vaccination, prevention of anemia and rickets. Issues of feeding young children are also discussed. Methodical recommendations are worked out on the basis of the Program of discipline of «Pediatrics» for students of higher medical educational institutions of III–IV levels of accreditation, authorized by Ministry of Health of Ukraine. These recommendations are intended for the 6th year English-speaking medical students.

В методичних рекомендаціях надано інформацію стосовно динамічного спостереження дітей віком до 3-х років в умовах поліклініки, яке включає оцінку фізичного та психомоторного розвитку, профілактичне щеплення, профілактику анемії та рахіту. Також обговорюються питання вигодовування дітей раннього віку. Методичні рекомендації розроблено на основі програми дисципліни «Педіатрія» для студентів вищих медичних навчальних закладів III–IV рівнів акредитації, затвердженої МОЗ України. Дані рекомендації призначені для студентів 6-го курсу медичного факультету англомовного навчання.
Медичне спостереження дітей перших трьох років життя в поліклініці : методичні рекомендації для студентів 6го курсу медичного факультету
Навчальне видання
Keywords: MEDICINE; SOCIAL SCIENCES; children; physical development; psуchomotor development; feeding; prevention; діти; фізичний розвиток; психомоторний розвиток; вигодовування; профілактика